Investigation of the bedding effect on coal rock under Brazilian splitting tests - Hu, Jie; Zhang, Longfei; He, Manchao (Frontiers in Earth Science, 2024)
This contribution focuses on understanding the bedding effect of coal rock under Brazilian splitting test. Firstly, Multiple Brazilian splitting tests were performed on coal rock with various bedding angles to systematically investigate the influence of stratification. Subsequently, numerical models with stratified structures were constructed, and a continuous-discontinuous numerical analysis method based on the cohesive zone model (CZM) was employed to conduct the corresponding numerical investigations. Results indicate that the load-displacement curves of coal rock specimens with different bedding angles can be classified into four stages: initial compaction stage, elastic deformation stage, crack rapid coalescence stage, and final destruction stage. As the bedding angle increases, the failure patterns of coal rock specimens can be categorized into three groups: (1) Stretching damage along bedding planes. (2) Mixed tension and shear failure along the bedding planes and the coal matrix. (3) Stretching failure passing through the coal matrix. Furthermore, the tensile strength and cumulative AE energy-displacement relations are significantly influenced by the bedding angle. The numerical model can effectively predict the mechanical responses and fracture behavior of coal rock specimens, providing empirical parameters for the simulation of similar rock engineering.